Alessandro e Clito (Suda μ 720 + οι 178 Adler) - Favuzzi, Andrea (Histos, 2014)
This paper deals with an anonymous quotation in the Suda-Lexicon (μ 720 Adler) concerning the murder of Cleitus by Alexander the Great. The quotation, which at first sight seems sound, in fact conceals a textual corruption. After reviewing the different constructions of the verb διελαύνω and focusing on a detail of the story that is handed down only by Curtius Rufus, the paper proposes a textual emendation which makes better sense of the whole context. This context also includes another anonymous quotation (οι 178), which is evidently a continuation of the first one. The combination of the two quotations provides a single fragment which can be confidently be attributed to Aelian—one of the direct sources of the Suda-Lexicon—on the basis both of linguistic criteria and of content.